Eye Movements Modulate the Spatiotemporal Dynamics of Word Processing - Temereanca, Simona (Society for Neuroscience, 2012)
Active reading requires coordination between frequent eye movements (saccades) and short fixations in text. Yet, the impact of saccades on word processing remains unknown, as neuroimaging studies typically employ constant eye fixation. Here we investigate eye-movement effects on word recognition processes in healthy human subjects using anatomically constrained magnetoencephalography, psychophysical measurements, and saccade detection in real time. Word recognition was slower and brain responses were reduced to words presented early versus late after saccades, suggesting an overall transient impairment of word processing after eye movements. Response reductions occurred early in visual cortices and later in language regions, where they colocalized with repetition priming effects. Qualitatively similar effects occurred when words appeared early versus late after background movement that mimicked saccades, suggesting that retinal motion contributes to postsaccadic inhibition. Further, differences in postsaccadic and background-movement effects suggest that central mechanisms also contribute to postsaccadic modulation. Together, these results suggest a complex interplay between visual and central saccadic mechanisms during reading.